Preliminary Eye Check-Up and Appointment System - Anandarajah, Lagindran (IRC, 2020)
Preliminary Eye Check Up and Appointment system is an application to perform preliminary eye tests and manages appointments with eye doctors for consultations. This application is a webbased application system. The main reason for me to come up with this project is to provide an automated eye tests and appointment booking system which is organized and flexible. Moreover, this project is developed to ease the current appointment system thus to save appointment time between eye doctors and patients. Currently, eye clinics still implementing manual methods such as booking via phone calls or emails. Patients who visits without any appointments need to wait for their turns to meet the doctor for consultations. Moreover, preliminary eye tests will be conducted by doctors on the consultation period. Patients will be given an appointment cards with next appointment date written and appointments will be noted by receptionists in a log book. This method is no longer efficient because there are many problems occurs such as consultation hours are time consuming, poor organization of appointments, loss of appointment cards by patients. Since this is a web-based platform system, C # is the programming language and the project is built under the framework of ASP.Net. The software development approach used in this project is phased development due to quick implementation and short time schedule.